2018
DOI: 10.1186/s12968-018-0453-z
|View full text |Cite
|
Sign up to set email alerts
|

3D whole-brain vessel wall cardiovascular magnetic resonance imaging: a study on the reliability in the quantification of intracranial vessel dimensions

Abstract: BackgroundOne of the potentially important applications of three-dimensional (3D) intracranial vessel wall (IVW) cardiovascular magnetic resonance (CMR) is to monitor disease progression and regression via quantitative measurement of IVW morphology during medical management or drug development. However, a prerequisite for this application is to validate that IVW morphologic measurements based on the modality are reliable. In this study we performed comprehensive reliability analysis for the recently proposed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 34 publications
(45 reference statements)
2
39
0
Order By: Relevance
“…Analysis of inter-observer reproducibility is an essential requirement for validation of an imaging modality. Zhang et al [27] previously performed a comprehensive reliability analysis for the 3D wholebrain CMR VWI technique. However, this study was limited by the small sample size of clinical patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of inter-observer reproducibility is an essential requirement for validation of an imaging modality. Zhang et al [27] previously performed a comprehensive reliability analysis for the 3D wholebrain CMR VWI technique. However, this study was limited by the small sample size of clinical patients.…”
Section: Discussionmentioning
confidence: 99%
“…The morphologic measurements, including the lumen diameter of the CCA and segments C1-C7, and the stenosis diameter, stenosis degree, reference diameter, and lesion length, as measured by 3D CMR VWI, displayed excellent accordance with those measured by DSA (ICC > 0.84). One possible reason for the excellent performance of the 3D CMR VWI technique is that a non-selective excitation radio-frequency pulse has been used to shorten the echo time, which helps improve the SNR of images [23,24,27]. Additionally, 3D CMR VWI provided a high isotropic resolution of 0.63 × 0.63 × 0.63 mm 3 , and achieves good flexibility with regard to image visualization, which thereby enables the visualization of plaques located in the tortuous and deep-seated intracranial carotid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For subjects who were diagnosed with ICAD ( n > 200), the clinical follow‐up will be conducted at 3, 6, 12, and 24 months and the MR imaging follow‐up will be performed at 12 and 24 months, respectively. Previous studies reported that the progression rate of ICAS was 3.86% per year (Ryu et al., ) and the intra‐reader and inter‐scan variation in measuring maximum wall thickness of intracranial plaques was 6.67% (Zhang et al., ). Therefore, it might be reasonable to detect the 2 years’ progression of intracranial atherosclerosis disease (7.72%) which is greater than the variation of quantitative measurement by MRI.…”
Section: Methodsmentioning
confidence: 97%